PENGARUH SENAM LANSIA TERHADAP KESEHATAN REPRODUKSI DAN KUALITAS HIDUP PADA LANJUT USIA DI PUSKESMAS BANJARMASIN INDAH: PENGARUH SENAM LANSIA TERHADAP KESEHATAN REPRODUKSI DAN KUALITAS HIDUP PADA LANJUT USIA DI PUSKESMAS BANJARMASIN INDAH - Cahyani Ari Lestari, Nur; Wahyu Utami, Syahrida (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2025)
This study aims to analyze the effect of elderly exercise (senam lansia) on reproductive health and quality of life among elderly population in Posyandu Lansia Sejahtera. This quasi-experimental research employed a one-group pretest-posttest design with 72 elderly participants aged 60-75 years who were selected through purposive sampling. The intervention consisted of structured elderly exercise performed twice weekly for 12 weeks. Data were collected using reproductive health questionnaires and WHOQOL-BREF instruments before and after the intervention. Data analysis used paired t-test and Wilcoxon signed-rank test. Results showed significant improvements in reproductive health parameters including urinary incontinence symptoms (p=0.001), vaginal/penile dryness (p=0.003), pelvic muscle strength (p<0.001), and overall quality of life (p<0.001) after regular participation in elderly exercise. The most significant improvements were observed in physical domain scores (mean increase 8.74 points, p<0.001). The study concludes that regular elderly exercise positively affects reproductive health and quality of life in the elderly population. Healthcare providers are recommended to incorporate elderly exercise as a standard intervention in elderly reproductive health management programs.